Emergency Transfer of Acute Stroke Patients within the East Saxony Telemedicine Stroke Network: A Descriptive Analysis. Issue 2 (February 2014) - Kepplinger, Jessica; Dzialowski, Imanuel; Barlinn, Kristian; Puetz, Volker; Wojciechowski, Claudia; Schneider, Hauke; Gahn, Georg; Back, Tobias; Schackert, Gabriele; Reichmann, Heinz; von Kummer, Ruediger; Bodechtel, Ulf
Background: Telemedicine may facilitate the selection of stroke patients who require emergency transfer to a comprehensive stroke center to receive additional therapies other than intravenous tissue plasminogen activator. Aims and/or hypothesis: We sought to analyze frequency, patient characteristics, and specific therapies among emergently transferred patients within the telemedical Stroke East Saxony Network. Methods: We reviewed consecutive patients who were transferred emergently from remote spoke sites to hub sites. Certified stroke neurologists performed teleconsultations 24/7, with access to high-speed videoconferencing and transfer of brain images. Emergent transfers were initiated when considered necessary by the stroke neurologist. Results: In 2009 and 2010, we conducted 1413 teleconsultations and subsequently recommended transfer in 339 (24%) patients [mean age 64 ± 14 years, 54% males, median National Institutes of Health Stroke Scale score 5 (interquartile range, IQR 12). The mean teleconsultation-to-arrival time was 1·7 ± 0·8 h (median 1·6 h). Sixty-eight (20%) transferred patients had a nonstroke diagnosis. The remaining 271 (80%) patients had stroke diagnoses [ischemic stroke, 114 (34%); transient ischemic attack, 8 (2%); and intracranial haemorrhage, 149 (44%)]. Forty (35%) ischemic stroke patients received tissue plasminogen activator at spoke sites ('drip and ship'). Of the 240 stroke patients emergently transferred to the main hub site, 119 (49·6%) received at least one specific stroke therapy. Conclusion: A remarkable number of stroke patients can be transferred within a telemedical network to enable the delivery of specific stroke therapies that require advanced multispecialty expertise. Whether associated logistic efforts and costs have an impact on patients' clinical outcomes needs to be evaluated.